Hydrophobic PHBV composite fiber and preparation method thereof

By mixing PHBV with polylactic acid and composite nanocellulose in the textile field and introducing nanosilver, the thermal stability and antibacterial properties of PHBV composite materials were solved, and hydrophobic PHBV composites with high mechanical strength and antibacterial properties were prepared. Fiber realizes the effective application of composite materials in the textile field.

CN119145085AActive Publication Date: 2024-12-17NANJING BIOSERICA ERA ANTIMICROBIAL MATERIALS TECHNOLOGY GROUP CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411392916.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2024-12-17
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

The existing PHBV composite materials have problems such as poor thermal stability, narrow processing windows, poor hydrophobic and anti-bacterial properties in the textile field, which limits their application.

Method used

Hydrophobic PHBV composite fibers were prepared by mixing PHBV with polylactic acid and composite nanocellulose by melt extrusion and spinning, and nanosilver was introduced as antibacterial agent, using transesterification catalyst and maleic anhydride as compatibilizer, and performing Transesterification reaction and Steglich esterification treatment improve the dispersion of nanosilver and the interfacial compatibility of composite fibers.

Benefits of technology

Hydrophobic PHBV composite fiber with high mechanical strength and good antibacterial properties is prepared, which has long-lasting antibacterial and hydrophobic properties, expanding its application range and service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of composite fibers, in particular to a hydrophobic PHBV composite fiber and a preparation method thereof.The preparation method comprises the steps that polylactic acid and PHBV are selected as composite fiber raw materials, and a transesterification catalyst and maleic anhydride are selected to be compounded to serve as a compatibilizer; the preparation method comprises the following steps: crushing microcrystalline cellulose to prepare nano-cellulose, then treating with sodium periodate to obtain aldehyde nano-cellulose, then adding a silver ammonia solution to synthesize silver-loaded nano-cellulose in situ, introducing unsaturated double bonds on the silver-loaded nano-cellulose with alkenyl succinic anhydride to obtain double-bond silver-loaded nano-cellulose, and then carrying out free radical polymerization to obtain the silver-loaded nano-cellulose composite material. Methacrylamide, octadecyl methacrylate, double-bond silver-loaded nanocellulose, double-bond syringaldehyde and hydroxyethyl methylacrylate are subjected to a reaction, and green, healthy, fluoride-free, hydrophobic, broad-spectrum and antibacterial composite nanocellulose with multiple active sites is prepared; the composite fiber is endowed with lasting antibacterial and hydrophobic characteristics, so that the application range and the service life of the composite fiber are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite fibers, in particular to a hydrophobic PHBV composite fiber and a preparation method thereof. Background Art

[0002] With the development of society and the promotion of concepts such as environmental protection and health, in the textile field, consumers' attention has gradually shifted from difficult-to-degrade chemical synthetic fibers to bio-based degradable materials. The development of degradable green composite materials is of great significance for solving environmental pollution. PHBV, the full name of which is poly (3-hydroxybutyric acid-co-3-hydroxyvaleric acid copolyester), is a degradable polymer material produced by biological fermentation. It has attracted widespread attention due to its good mechanical strength and degradability, but it also has defects such as poor thermal stability and narrow processing window, which limit its further application.

[0003] In the existing market, blending is usually chosen to improve the physical and mechanical properties of composite materials. However, when it is applied to the textile field, there are still problems such as poor hydrophobicity and antifouling properties and limited antibacterial properties. Summary of the invention

[0004] The object of the present invention is to provide a hydrophobic PHBV composite fiber and a preparation method thereof to solve the problems in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A method for preparing a hydrophobic PHBV composite fiber comprises the following steps:

[0007] S1: drying PHBV, polylactic acid, and composite nanocellulose, mixing PHBV, polylactic acid, composite nanocellulose, and a compatibilizer, and melt-extruding to obtain a blended masterbatch;

[0008] S2: After drying the blended masterbatch, melt spinning is performed to obtain raw yarn;

[0009] S3: The raw silk is sequentially drawn, curled and cut to obtain a hydrophobic PHBV composite fiber.

[0010] Furthermore, the mass content ratio of PHBV to polylactic acid in the blended masterbatch is 17-27%.

[0011] Furthermore, the mass content ratio of the composite nanocellulose and polylactic acid in the blended masterbatch is 6-9%; the mass content ratio of the compatibilizer and polylactic acid in the blended masterbatch is 2-4%.

[0012] Furthermore, the working conditions of melt extrusion are: screw speed of 80 r / min, working temperature of 180°C.

[0013] Furthermore, the working conditions of melt spinning are: spinning temperature of 190° C., screw speed of 45 r / min, spinneret diameter of 2 mm, and winding speed of 35 m / min.

[0014] Furthermore, the working conditions for drawing are: drawing temperature is 68-72°C, drawing multiple is 2.5-3 times, and winding speed is 190m / min.

[0015] Furthermore, the compatibilizer is prepared by compounding an ester exchange catalyst and maleic anhydride in a mass ratio of 1:2.

[0016] Furthermore, the preparation of composite nanocellulose includes the following steps:

[0017] (1) using an ultrasonic cell disruptor to treat microcrystalline cellulose to obtain nanocellulose; mixing nanocellulose and deionized water to prepare a nanocellulose suspension, adding sodium periodate, stirring for 22-24 hours in a dark environment, centrifuging, diluting with deionized water, ultrasonically dispersing, adding silver ammonia solution, ultrasonically shaking, transferring to a 38-42°C water bath and keeping warm for 10-20 minutes to obtain silver-loaded nanocellulose;

[0018] (2) mixing silver-loaded nanocellulose and N,N-dimethylacetamide, adding hexadecyltrimethylammonium bromide and sodium carbonate, keeping warm in a water bath for 50-60 minutes, adding alkenyl succinic anhydride, stirring for 5-6 hours, filtering, washing, soaking in hydrochloric acid for 8-10 minutes, washing with water until neutral, and obtaining double-bonded silver-loaded nanocellulose;

[0019] (3) Under a nitrogen atmosphere, methacrylamide, octadecyl methacrylate, double-bonded silver-loaded nanocellulose, double-bonded syringaldehyde, hydroxyethyl methacrylate, azobisisobutyronitrile, and N,N-dimethylformamide are mixed, the temperature is raised to 68-72°C and kept warm for 4-6 hours, deionized water is added, and the mixture is dried to obtain composite nanocellulose.

[0020] Further, the preparation of double-bonded syringaldehyde comprises the following steps:

[0021] Under a nitrogen atmosphere, vanillin and 4-dimethylaminopyridine are mixed, methacrylic anhydride is added, the temperature is raised to 48-52°C and kept warm for 22-24 hours, 15 mL of dichloromethane is added, and the mixture is washed with a saturated sodium bicarbonate aqueous solution until there are no bubbles, and then washed with a sodium hydroxide aqueous solution and a hydrochloric acid aqueous solution for 1-3 times, and anhydrous magnesium sulfate is added for drying, and the mixture is filtered, distilled under reduced pressure, and dried to obtain double-bonded vanillin.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The invention provides a hydrophobic PHBV composite fiber and a preparation method thereof. The hydrophobic PHBV composite fiber with high mechanical strength and good antibacterial property is prepared by optimizing components and processes.

[0024] The biodegradable polymer polylactic acid is selected to be blended with PHBV to prepare the composite fiber, and an ester exchange catalyst and maleic anhydride are used as a compatibilizer to improve the compatibility of the two. While overcoming the inherent brittleness of polylactic acid, the mechanical strength and thermal stability of PHBV are improved.

[0025] In order to give the composite fiber excellent antibacterial properties, nanosilver is introduced as an antibacterial agent in the present invention. In order to improve the uniformity of the dispersion of nanosilver in the fiber, the present invention first crushes microcrystalline cellulose to prepare nanocellulose, then treats it with sodium periodate to obtain aldehyde-modified nanocellulose, and then adds silver ammonia solution to synthesize silver-loaded nanocellulose in situ, thereby solving the problem of easy agglomeration of nanosilver. The silver-loaded nanocellulose is compounded with PHBV and polylactic acid, which not only exerts the reinforcing effect of nanocellulose, but also gives the composite fiber antibacterial properties.

[0026] In order to further improve the interfacial compatibility between silver-loaded nanocellulose and composite fibers, make the silver-loaded nanocellulose firmly bonded in the composite fibers and provide them with lasting antibacterial and hydrophobic properties, the silver-loaded nanocellulose was modified. First, unsaturated double bonds were introduced into the silver-loaded nanocellulose using alkenyl succinic anhydride to obtain double-bonded silver-loaded nanocellulose. Then, free radical polymerization was used to react methacrylamide, octadecyl methacrylate, double-bonded silver-loaded nanocellulose, double-bonded syringaldehyde and hydroxyethyl methacrylate to prepare green, healthy, fluorine-free, hydrophobic, broad-spectrum antibacterial composite nanocellulose with multiple active sites. The double-bonded syringaldehyde was prepared by using biomass-based vanillin with antibacterial properties as raw material and double-bonded by Steglich esterification. The introduction of double-bonded syringaldehyde not only cooperated with nanosilver to achieve broad-spectrum antibacterial effects, but also improved the bonding strength between the composite nanocellulose and the base material, thereby giving the composite fiber lasting antibacterial and hydrophobic properties, thereby improving the use range and life of the composite fiber. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, and back, the directional indication is only used to explain a specific posture such as the relative position relationship between the components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.

[0029] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.

[0030] Embodiment 1: A method for preparing a hydrophobic PHBV composite fiber, comprising the following steps:

[0031] S1: drying PHBV, polylactic acid, and composite nanocellulose, mixing PHBV, polylactic acid, composite nanocellulose, and a compatibilizer, and melt-extruding to obtain a blended masterbatch;

[0032] The mass content ratio of PHBV to polylactic acid in the blended masterbatch is 17%;

[0033] The mass content ratio of composite nanocellulose and polylactic acid in the blended masterbatch is 6%;

[0034] The mass content ratio of the compatibilizer and the polylactic acid in the blended masterbatch is 2%;

[0035] The working conditions of melt extrusion are: screw speed 80r / min, working temperature 180°C;

[0036] The compatibilizer is prepared by mixing an ester exchange catalyst and maleic anhydride in a mass ratio of 1:2;

[0037] The preparation of the composite nanocellulose comprises the following steps:

[0038] (1) Using an ultrasonic cell disruptor to treat microcrystalline cellulose to obtain nanocellulose; mixing nanocellulose and deionized water to prepare 100 mL of a nanocellulose suspension with a mass concentration of 1%, adding 1 g of sodium periodate, stirring for 22 h in a dark environment, centrifuging, diluting to 100 mL with deionized water, ultrasonically dispersing, adding 10 drops of saturated silver ammonia solution, ultrasonically shaking, transferring to a 38°C water bath and keeping warm for 10 min to obtain silver-loaded nanocellulose;

[0039] (2) 6 g of silver-loaded nanocellulose and 50 mL of N,N-dimethylacetamide were mixed, 0.3 g of hexadecyltrimethylammonium bromide and 1.6 g of sodium carbonate were added, the mixture was kept in a water bath for 50 min, 1.2 g of alkenylsuccinic anhydride was added, the mixture was stirred for 5 h, filtered, washed, soaked in 100 mL of 1 mol / L hydrochloric acid for 8 min, and washed with water until neutral to obtain double-bonded silver-loaded nanocellulose;

[0040] (3) Under nitrogen atmosphere, 2.4 g of methacrylamide, 6.2 g of octadecyl methacrylate, 4.7 g of double-bonded silver-loaded nanocellulose, 4.1 g of double-bonded syringaldehyde, 2.6 g of hydroxyethyl methacrylate, 0.5 g of azobisisobutyronitrile, and 30 mL of N,N-dimethylformamide were mixed, the temperature was raised to 68 °C and kept warm for 6 h, 50 mL of deionized water was added, and the mixture was dried to obtain composite nanocellulose;

[0041] The preparation of the double-bonded syringaldehyde comprises the following steps:

[0042] Under a nitrogen atmosphere, 9.5 g of vanillin and 0.1 g of 4-dimethylaminopyridine were mixed, 9.6 g of methacrylic anhydride was added, the temperature was raised to 48 ° C and kept for 24 h, 15 mL of dichloromethane was added, and the mixture was washed with a saturated sodium bicarbonate aqueous solution until there were no bubbles, and then washed with a sodium hydroxide aqueous solution and a hydrochloric acid aqueous solution once, and anhydrous magnesium sulfate was added to dry, and then filtered, vacuum distilled, and dried to obtain double-bonded vanillin;

[0043] S2: After drying the blended masterbatch, melt spinning is performed to obtain raw yarn;

[0044] The working conditions of melt spinning were: spinning temperature of 190 °C, screw speed of 45 r / min, spinneret diameter of 2 mm, and winding speed of 35 m / min;

[0045] S3: The raw silk is sequentially drawn, curled and cut to obtain a hydrophobic PHBV composite fiber; the drawing working conditions are: drawing temperature of 68°C, drawing multiple of 2.5 times, and winding speed of 190m / min.

[0046] Embodiment 2: A method for preparing a hydrophobic PHBV composite fiber, comprising the following steps:

[0047] S1: drying PHBV, polylactic acid, and composite nanocellulose, mixing PHBV, polylactic acid, composite nanocellulose, and a compatibilizer, and melt-extruding to obtain a blended masterbatch;

[0048] The mass content ratio of PHBV to polylactic acid in the blended masterbatch is 21%;

[0049] The mass content ratio of composite nanocellulose and polylactic acid in the blended masterbatch is 7.2%;

[0050] The mass content ratio of the compatibilizer and the polylactic acid in the blended masterbatch is 3%;

[0051] The working conditions of melt extrusion are: screw speed 80r / min, working temperature 180°C;

[0052] The compatibilizer is prepared by mixing an ester exchange catalyst and maleic anhydride in a mass ratio of 1:2;

[0053] The preparation of the composite nanocellulose comprises the following steps:

[0054] (1) Using an ultrasonic cell disruptor to treat microcrystalline cellulose to obtain nanocellulose; mixing nanocellulose and deionized water to prepare 100 mL of a nanocellulose suspension with a mass concentration of 1%, adding 1 g of sodium periodate, stirring for 23 h in a dark environment, centrifuging, diluting to 100 mL with deionized water, ultrasonically dispersing, adding 10 drops of saturated silver ammonia solution, ultrasonically shaking, transferring to a 40°C water bath and keeping warm for 15 min to obtain silver-loaded nanocellulose;

[0055] (2) 6 g of silver-loaded nanocellulose and 50 mL of N,N-dimethylacetamide were mixed, 0.3 g of hexadecyltrimethylammonium bromide and 1.6 g of sodium carbonate were added, the mixture was kept in a water bath for 55 min, 1.2 g of alkenylsuccinic anhydride was added, the mixture was stirred for 5.5 h, filtered, washed, soaked in 100 mL of 1 mol / L hydrochloric acid for 9 min, and washed with water until neutral to obtain double-bonded silver-loaded nanocellulose;

[0056] (3) Under a nitrogen atmosphere, 2.4 g of methacrylamide, 6.2 g of octadecyl methacrylate, 4.7 g of double-bonded silver-loaded nanocellulose, 4.1 g of double-bonded syringaldehyde, 2.6 g of hydroxyethyl methacrylate, 0.5 g of azobisisobutyronitrile, and 30 mL of N,N-dimethylformamide were mixed, the temperature was raised to 70 °C and kept for 5 h, 50 mL of deionized water was added, and the mixture was dried to obtain composite nanocellulose;

[0057] The preparation of the double-bonded syringaldehyde comprises the following steps:

[0058] Under a nitrogen atmosphere, 9.5 g of vanillin and 0.1 g of 4-dimethylaminopyridine were mixed, 9.6 g of methacrylic anhydride was added, the temperature was raised to 50 ° C and kept for 23 h, 15 mL of dichloromethane was added, and the mixture was washed with a saturated sodium bicarbonate aqueous solution until there were no bubbles, and then washed twice with a sodium hydroxide aqueous solution and a hydrochloric acid aqueous solution, and dried with anhydrous magnesium sulfate, filtered, distilled under reduced pressure, and dried to obtain double-bonded vanillin;

[0059] S2: After drying the blended masterbatch, melt spinning is performed to obtain raw yarn;

[0060] The working conditions of melt spinning were: spinning temperature of 190 °C, screw speed of 45 r / min, spinneret diameter of 2 mm, and winding speed of 35 m / min;

[0061] S3: The raw silk is sequentially drawn, curled and cut to obtain a hydrophobic PHBV composite fiber; the drawing working conditions are: drawing temperature of 70°C, drawing multiple of 2.7 times, and winding speed of 190m / min.

[0062] Embodiment 3: A method for preparing a hydrophobic PHBV composite fiber, comprising the following steps:

[0063] S1: drying PHBV, polylactic acid, and composite nanocellulose, mixing PHBV, polylactic acid, composite nanocellulose, and a compatibilizer, and melt-extruding to obtain a blended masterbatch;

[0064] The mass content ratio of PHBV to polylactic acid in the blended masterbatch is 27%;

[0065] The mass content ratio of composite nanocellulose and polylactic acid in the blended masterbatch is 9%;

[0066] The mass content ratio of the compatibilizer and the polylactic acid in the blended masterbatch is 4%;

[0067] The working conditions of melt extrusion are: screw speed 80r / min, working temperature 180°C;

[0068] The compatibilizer is prepared by mixing an ester exchange catalyst and maleic anhydride in a mass ratio of 1:2;

[0069] The preparation of the composite nanocellulose comprises the following steps:

[0070] (1) Using an ultrasonic cell disruptor to treat microcrystalline cellulose to obtain nanocellulose; mixing nanocellulose and deionized water to prepare 100 mL of a nanocellulose suspension with a mass concentration of 1%, adding 1 g of sodium periodate, stirring for 24 h in a dark environment, centrifuging, diluting to 100 mL with deionized water, ultrasonically dispersing, adding 10 drops of saturated silver ammonia solution, ultrasonically shaking, transferring to a 42°C water bath and keeping warm for 10 min to obtain silver-loaded nanocellulose;

[0071] (2) 6 g of silver-loaded nanocellulose and 50 mL of N,N-dimethylacetamide were mixed, 0.3 g of hexadecyltrimethylammonium bromide and 1.6 g of sodium carbonate were added, the mixture was kept in a water bath for 60 min, 1.2 g of alkenylsuccinic anhydride was added, the mixture was stirred for 6 h, filtered, washed, soaked in 100 mL of 1 mol / L hydrochloric acid for 10 min, and washed with water until neutral to obtain double-bonded silver-loaded nanocellulose;

[0072] (3) Under a nitrogen atmosphere, 2.4 g of methacrylamide, 6.2 g of octadecyl methacrylate, 4.7 g of double-bonded silver-loaded nanocellulose, 4.1 g of double-bonded syringaldehyde, 2.6 g of hydroxyethyl methacrylate, 0.5 g of azobisisobutyronitrile, and 30 mL of N,N-dimethylformamide were mixed, the temperature was raised to 72 °C and kept for 4 h, 50 mL of deionized water was added, and the mixture was dried to obtain composite nanocellulose;

[0073] The preparation of the double-bonded syringaldehyde comprises the following steps:

[0074] Under a nitrogen atmosphere, 9.5 g of vanillin and 0.1 g of 4-dimethylaminopyridine were mixed, 9.6 g of methacrylic anhydride was added, the temperature was raised to 52 ° C and kept for 22 h, 15 mL of dichloromethane was added, and the mixture was washed with a saturated sodium bicarbonate aqueous solution until there were no bubbles, and then washed with a sodium hydroxide aqueous solution and a hydrochloric acid aqueous solution for 3 times, and anhydrous magnesium sulfate was added to dry, and then filtered, distilled under reduced pressure, and dried to obtain double-bonded vanillin;

[0075] S2: After drying the blended masterbatch, melt spinning is performed to obtain raw yarn;

[0076] The working conditions of melt spinning were: spinning temperature of 190 °C, screw speed of 45 r / min, spinneret diameter of 2 mm, and winding speed of 35 m / min;

[0077] S3: The raw silk is sequentially drawn, curled and cut to obtain a hydrophobic PHBV composite fiber; the drawing working conditions are: drawing temperature of 72°C, drawing multiple of 3 times, and winding speed of 190m / min.

[0078] Comparative Example 1: Taking Example 3 as the control group, the composite nanocellulose was replaced with silver-loaded nanocellulose, and the other processes were normal.

[0079] Comparative Example 2: Example 3 was used as a control group, in which double-bonded syringaldehyde was not prepared, and other processes were normal.

[0080] Sources of raw materials used (for demonstration purposes only):

[0081] PHBVY1000P: Nanjing Hesu Times Antibacterial Materials Technology Group Co., Ltd.; Polylactic acid 032563: Hubei Shiteng Chemical Technology Co., Ltd.; Maleic anhydride (99%): Shandong Qiangsen Chemical Co., Ltd.; Silver ammonia solution JK8197: Shanghai Jingkang Bioengineering Co., Ltd.; Transesterification catalyst (zinc acetate) Z110777, microcrystalline cellulose C104844, sodium periodate S104091, N,N-dimethylacetamide D108096, hexadecyltrimethylammonium bromide C274355, alkenyl succinic acid Anhydride (dodecenylsuccinic anhydride) D351109, methacrylamide M104042, octadecyl methacrylate S107562, hydroxyethyl methacrylate H140643, azobisisobutyronitrile A434183, N,N-dimethylformamide D111999, vanillin V100115, 4-dimethylaminopyridine D109207, methacrylic anhydride M102519: Aladdin reagent; sodium carbonate, hydrochloric acid, dichloromethane, sodium bicarbonate, sodium hydroxide, anhydrous magnesium sulfate, analytical grade: Sinopharm reagent.

[0082] Performance test: The composite fibers prepared in the embodiments and comparative examples were tested:

[0083] Dry elongation at break: refer to GB / T14337-2022, the working temperature is 25℃, the test is carried out using a constant-speed elongation single fiber tensile tester, the stretching speed is 50mm / min, and each sample is tested 10 times to take the average value;

[0084] Sample preparation: The prepared composite fiber was used to weave a single-layer plain weave fabric on a sample loom, with a warp density of 540 strands / 10cm, a weft density of 480 strands / 10cm, and a square meter weight of 105g / m 2 ;

[0085] Hydrophobicity: The prepared samples were tested for water contact angle using a tester, using a 2µL deionized water droplet;

[0086] Antibacterial persistence: Tested with reference to ATCC100-2004, the sample was cut into 2.54cm in length and width and placed on a petri dish, 25µL of bacterial solution was added, and the sample of the same size was covered. Gravity was applied to keep the two fabrics close together for 10 minutes, 5mL of 0.02N sodium thiosulfate solution was added to the petri dish, the petri dish was covered and vortexed, diluted with phosphate buffer solution, and the dilution was placed in the culture medium, cultured at 37°C for 24 hours, the number of surviving bacteria was counted, and the corresponding antibacterial rate was calculated. The sample was tested after 20 standard water washes, and ATCC6538 Staphylococcus aureus was selected as the test strain; the results are shown in Table 1;

[0087] Table 1

[0088]

[0089] The invention provides a hydrophobic PHBV composite fiber and a preparation method thereof. The hydrophobic PHBV composite fiber with high mechanical strength and good antibacterial property is prepared by optimizing components and processes.

[0090] By comparing Example 3 with Comparative Examples 1 and 3, it can be seen that in order to give the composite fiber excellent antibacterial properties, nanosilver is introduced as an antibacterial agent in the present invention. In order to improve the uniformity of the dispersion of nanosilver in the fiber, the present invention first crushes microcrystalline cellulose to prepare nanocellulose, then treats it with sodium periodate to obtain aldehyde-modified nanocellulose, and then adds silver ammonia solution to synthesize silver-loaded nanocellulose in situ, thereby solving the problem of easy agglomeration of nanosilver. The silver-loaded nanocellulose is compounded with PHBV and polylactic acid, which not only exerts the reinforcing effect of nanocellulose, but also gives the composite fiber antibacterial properties.

[0091] In order to further improve the interfacial compatibility between silver-loaded nanocellulose and composite fibers, make the silver-loaded nanocellulose firmly bonded in the composite fibers and provide them with long-lasting antibacterial and hydrophobic properties, the silver-loaded nanocellulose was modified. First, unsaturated double bonds were introduced into the silver-loaded nanocellulose with alkenyl succinic anhydride to obtain double-bonded silver-loaded nanocellulose. Then, free radical polymerization was used to react methacrylamide, octadecyl methacrylate, double-bonded silver-loaded nanocellulose, double-bonded syringaldehyde and hydroxyethyl methacrylate to prepare green, healthy, fluorine-free, hydrophobic, broad-spectrum antibacterial and composite nanocellulose with multiple active sites. The double-bonded syringaldehyde was prepared by using biomass-based vanillin with antibacterial properties as raw material and Steglich esterification to double-bond it. The introduction of double-bonded syringaldehyde not only cooperated with nanosilver to achieve broad-spectrum antibacterial effects, but also improved the bonding strength between the composite nanocellulose and the base material, thereby giving the composite fiber long-lasting antibacterial and hydrophobic properties, thereby improving the use range and life of the composite fiber.

[0092] The above descriptions are only embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.

Claims

1. A method for preparing a hydrophobic PHBV composite fiber, characterized in that: The following steps are involved: S1: drying PHBV, polylactic acid, and composite nanocellulose, mixing PHBV, polylactic acid, composite nanocellulose, and a compatibilizer, and melt-extruding to obtain a blended masterbatch; S2: After drying the blended masterbatch, melt spinning is performed to obtain raw yarn; S3: The raw silk is sequentially drawn, curled and cut to obtain a hydrophobic PHBV composite fiber.

2. The method for preparing a hydrophobic PHBV composite fiber according to claim 1, characterized in that: The mass content ratio of PHBV to polylactic acid in the blended masterbatch is 17-27%.

3. The method for preparing a hydrophobic PHBV composite fiber according to claim 1, characterized in that: The mass content ratio of composite nanocellulose and polylactic acid in the blended masterbatch is 6-9%; the mass content ratio of compatibilizer and polylactic acid in the blended masterbatch is 2-4%.

4. The method for preparing a hydrophobic PHBV composite fiber according to claim 1, characterized in that: The working conditions of melt extrusion are: screw speed of 80r / min and working temperature of 180°C.

5. The method for preparing a hydrophobic PHBV composite fiber according to claim 1, characterized in that: The working conditions of melt spinning are: spinning temperature of 190°C, screw speed of 45 r / min, spinneret diameter of 2 mm, and winding speed of 35 m / min.

6. The method for preparing a hydrophobic PHBV composite fiber according to claim 1, characterized in that: The working conditions for drawing are: drawing temperature is 68-72°C, drawing multiple is 2.5-3 times, and winding speed is 190m / min.

7. The method for preparing a hydrophobic PHBV composite fiber according to claim 1, characterized in that: The compatibilizer is prepared by mixing an ester exchange catalyst and maleic anhydride in a mass ratio of 1:

2.

8. The method for preparing a hydrophobic PHBV composite fiber according to claim 1, characterized in that: The preparation of the composite nanocellulose comprises the following steps: (1) using an ultrasonic cell disruptor to treat microcrystalline cellulose to obtain nanocellulose; mixing nanocellulose and deionized water to prepare a nanocellulose suspension, adding sodium periodate, stirring for 22-24 hours in a dark environment, centrifuging, diluting with deionized water, ultrasonically dispersing, adding silver ammonia solution, ultrasonically shaking, transferring to a 38-42°C water bath and keeping warm for 10-20 minutes to obtain silver-loaded nanocellulose; (2) mixing silver-loaded nanocellulose and N,N-dimethylacetamide, adding hexadecyltrimethylammonium bromide and sodium carbonate, keeping warm in a water bath for 50-60 minutes, adding alkenyl succinic anhydride, stirring for 5-6 hours, filtering, washing, soaking in hydrochloric acid for 8-10 minutes, washing with water until neutral, and obtaining double-bonded silver-loaded nanocellulose; (3) Under a nitrogen atmosphere, methacrylamide, octadecyl methacrylate, double-bonded silver-loaded nanocellulose, double-bonded syringaldehyde, hydroxyethyl methacrylate, azobisisobutyronitrile, and N,N-dimethylformamide are mixed, the temperature is raised to 68-72°C and kept warm for 4-6 hours, deionized water is added, and the mixture is dried to obtain composite nanocellulose.

9. The method for preparing a hydrophobic PHBV composite fiber according to claim 8, characterized in that: The preparation of the double-bonded syringaldehyde comprises the following steps: Under a nitrogen atmosphere, vanillin and 4-dimethylaminopyridine are mixed, methacrylic anhydride is added, the temperature is raised to 48-52°C and kept warm for 22-24 hours, dichloromethane is added, the mixture is washed with a saturated sodium bicarbonate aqueous solution until there are no bubbles, and then washed with a sodium hydroxide aqueous solution and a hydrochloric acid aqueous solution for 1-3 times, anhydrous magnesium sulfate is added for drying, suction filtration, reduced pressure distillation, and drying to obtain double-bonded vanillin.

10. A hydrophobic PHBV composite fiber, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Biobased degradable fibers containing PHBV (poly<3-hydroxybutyrate-co-3-hydroxyvalerate>) and preparation method thereof

    CN102181960A

  • Fully-biodegradable composite membrane filled with nano silver / cellulose nanocrystal composite particles, and preparation method thereof

    CN103483786A

  • Preparation method of silver-loaded nano cellulose-chitosan composite film

    CN106832437A

  • Double-bonded vanillic aldehyde modified styrene-acrylic emulsion and preparation method thereof

    CN110563880A

  • Preparation method of polylactic acid / polycaprolactone antibacterial blend fiber

    CN117328162A